(untitled) (Fiep Bulletin - online, 2015)
It is known that it is possible to increase the strength of acutely by a prior stimulus of maximal muscle strength post-stimulation, this phenomenon is given the name of post-activation (PPA) .Objetivo potentiation: identify the acute effect PPA in the maximum strength of the upper limbs front of concentric, eccentric and combined in different with 95% concentric and eccentric maximum repetition (1RM), performed in the exercise protocols barbell muscle actions. Methodology: the study involved eight female subjects (39.9 ± 9.5 years, 72.0 ± 14.7 kg, 160.9 ± 5.0 cm), were localized exercise to two years in SESI Guaxupé MG. Four protocols were used to assess the acute effects of PPA at full strength in the exercise barbell - PC / C: concentric protocol performed at 95% 1RM concentric; PCE / C: concentric / eccentric protocol performed at 95% 1RM concentric; PE / C: eccentric protocol performed at 95% 1RM concentric; PE / E: eccentric protocol performed at 95% 1RM eccentric. All protocols were three repetitions with 95% of 1RM load concentric or eccentric. For data analysis we used the mean, standard deviation and to compare the means testing of ANOVA with post hoc Tukey test using SPSS software version 20. The level of significance was p <0.05. Result: after the completion of the protocols found increased strength in pre moment to moment after 17.2% in charge of the 1RM test for PC / C, appears to be significantly more efficient generation of PPA when compared to other protocols (p <0.01). Conclusion: It is recommended to use the PC / C to increase strength acutely since this is more efficient for the emergence of the phenomenon of PPA.